A SURVEY ON CONTINUOUS POSTGRADUATE DISASTER MEDICINE EDUCATION NEEDS IN THE PLOVDIV REGION - Elena Valkanova; Rostislav Kostadinov; Rumyana Etova; Mariya Georgieva; Maria Semerdjieva (Peytchinski Publishing, 2024)
Introduction: Disasters, regardless of their origin, have a direct negative impact on the physical and psychological wellbeing of the population. Medical support for the casualties necessitates specific organization and training of medical personnel. Knowledge and skills in the field are considered to be essential for the execution of a rapid response. Purpose: The aim of this research was to study the need for postgraduate disaster medicine education for different categories of medical professionals in the Plovdiv region. Materials and methods: A cross-sectional study was conducted in 2020 through an anonymous inquiry among medical professionals from pre-hospital healthcare, hospital care and the centers for emergency medical aid in the Plovdiv region. Results: The survey was held among 160 medical professionals. They were interviewed regarding their participation in medical support for disasters or mass casualty incidents. 50,3% of them had such experience. 65% of the respondents evaluated their knowledge of disaster medicine as moderate, while only 18,7% reported high self-assessment. Most interviewees knew the knowledge and skills needed for disaster medical support, but half had never trained in these skills. Almost all respondents - 93,1%, considered disaster medicine knowledge useful for medical practice. 89,4% share the opinion that postgraduate courses were necessary. 93,2% preferred to be trained and educated on the subject by the Medical University. Conclusions: The results from our survey highlight the lower than expected self-confidence among medical professionals regarding their disaster medical support knowledge and skills. Postgraduate training could improve disaster resilience by increasing skill and confidence.